2006
DOI: 10.1007/s10165-006-0520-4
|View full text |Cite
|
Sign up to set email alerts
|

Anticyclic citrullinated peptide antibodies in juvenile idiopathic arthritis

Abstract: Anticyclic citrullinated peptide (anti-CCP) antibodies have been detected in patients with juvenile idiopathic arthritis (JRA), particularly in those with polyarticular JIA. We analyzed the presence of anti-CCP antibodies of the IgG class in sera of patients with defined juvenile idiopathic arthritis (JIA) of various subgroups. One hundred and fifty-nine serum samples were investigated. Forty-five patients were diagnosed with JIA (15 male and 30 female) aged 1.9-17.3 years (median 12.9, mean 11.0). Thirty-eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 11 publications
1
20
0
2
Order By: Relevance
“…In another rheumatic diseases, it was suggested that erosiv arthritis was strongly associated with the presence of anti-CCP antibodies, such as non-rheumatoid arthritis [8], in patients with systemic lupus erythematosus, who presented with polyarthritis [28] and in juvenil idiopathic arthritis [29]. We also found that anti-CCP levels were high in patients with RA.…”
Section: Discussionmentioning
confidence: 63%
“…In another rheumatic diseases, it was suggested that erosiv arthritis was strongly associated with the presence of anti-CCP antibodies, such as non-rheumatoid arthritis [8], in patients with systemic lupus erythematosus, who presented with polyarthritis [28] and in juvenil idiopathic arthritis [29]. We also found that anti-CCP levels were high in patients with RA.…”
Section: Discussionmentioning
confidence: 63%
“…Numerous studies have shown that IgM RF-positive polyarthritis patients have a higher prevalence of anti-CCP antibodies [36][37][38][39][40][41][42][43][44]45 We have also shown that the measurement of IgA, IgM, and IgG anti-CCP antibody isotypes early in the course of JIA may be beneficial to distinguish aggressive disease and possibly initiate more aggressive treatment earlier in those patients [48•]. These patients have been shown to have higher immune complex levels by the anti-Fc III method of detection and are noted to have increased disease activity [49•].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that JIA patients should not be tested routinely for anti-CCP antibodies. In another JIA study looking at anti-CCP antibodies, Brunner and Sitzmann [44] showed no statistical significance between anti-CCP antibodies and C-reactive protein or disease duration.…”
Section: Anticyclic Citrullinated Peptide Antibodiesmentioning
confidence: 97%
“…The presence of RF is most often seen in the polyarticular subtypes, but when present in oligoarticular patients it has been associated with early erosive disease, suggesting that an RF-positive status should be a subset of its own regardless of the number of joints involved 9. The prevalence of anti-cyclic citrullinated peptide (CCP) antibodies varies in polyarticular JIA but usually coincides with RF status 10. However, the results of a single study indicated that approximately 6% of RF-negative patients were also CCP positive and tended to be phenotypically and genetically different from RF-positive, CCP-positive patients, prompting the discussion for the need to reclassify patients not only on RF status but CCP status as well 11.…”
Section: Classificationmentioning
confidence: 99%